AKTUALISAI NILAI-NILAI MATAN KEYAKINAN DAN CITA-CITA HIDUP MUHAMMADIYAH (MKCH) DALAM PRAKTIK PENDIDIKAN MUHAMMADIYAH PADA ERA KONTEMPORER - Murdaningrum, Dewi; Soelailahi, Soelailahi; Dina Mardiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the existence of Muhammadiyah ideology in responding to the dynamics of social change, focusing on three key documents: the Preamble of the Articles of Association (Muqaddimah Anggaran Dasar), the Muhammadiyah Statement of Beliefs and Aspirations (Matan Keyakinan dan Cita-Cita Hidup Muhammadiyah), and Muhammadiyah Personality. This research employs a qualitative approach using library research and critical discourse analysis. The findings reveal that these three documents form an integrated ideological system. The Muqaddimah serves as a philosophical foundation, MKCH provides a framework of beliefs and goals, and Muhammadiyah Personality functions as a guideline for organizational identity. These documents enable Muhammadiyah to contextualize its values dynamically without losing its fundamental principles. The implementation is reflected in its social initiatives in education, healthcare, and economic empowerment. Therefore, Muhammadiyah’s ideological existence lies in its ability to transform transcendental values into adaptive and sustainable social actions.